2013
DOI: 10.1007/s00508-013-0343-1
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical bacillus Calmette-Guérin instillation therapy for non-muscle-invasive bladder cancer following solid organ transplantation

Abstract: BCG therapy is a safe option for patients with high-risk NMIBC following solid organ transplantation. However, there is a substantial risk of recurrence and progression. Urologists and patients considering BCG therapy should be aware of this and may consider early cystectomy. There is no evidence to support the need for prophylactic antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Because of the theoretically high risk of side effects such as sepsis in immunocompromised patients, BCG instillation is contraindicated in transplant recipients. However, there are a few case reports indicating that BCG instillation was performed without complication in such patients 22,23. According to our matching analysis comparing the treatment outcomes of bladder cancer, the progression rates of bladder cancer were significantly higher in KT recipients.…”
Section: Discussionmentioning
confidence: 73%
“…Because of the theoretically high risk of side effects such as sepsis in immunocompromised patients, BCG instillation is contraindicated in transplant recipients. However, there are a few case reports indicating that BCG instillation was performed without complication in such patients 22,23. According to our matching analysis comparing the treatment outcomes of bladder cancer, the progression rates of bladder cancer were significantly higher in KT recipients.…”
Section: Discussionmentioning
confidence: 73%
“…The incidence of adverse BCG effects in immunocompromised patients is unclear because of a paucity of data in the literature. However, several recent studies following immunocompromised patients who received intravesical BCG have reported similar incidences of adverse reactions compared to non‐immunocompromised patients . Likewise, bladder cancer response rates to intravesical BCG after 6‐months among immunocompromised patients is also similar to non‐immunocompromised patients .…”
Section: Discussionmentioning
confidence: 86%
“…However, several recent studies following immunocompromised patients who received intravesical BCG have reported similar incidences of adverse reactions compared to non-immunocompromised patients. [15][16][17][18][19][20][21][22] Likewise, bladder cancer response rates to intravesical BCG after 6-months among immunocompromised patients is also similar to non-immunocompromised patients. 21 The largest case series by Herr and Dalgbani followed 45 immunosuppressed patients, including 12 solid organ transplant patients treated with intravesical BCG for bladder cancer, and found that BCG therapy was well-tolerated with no reports of BCG-induced sepsis.…”
Section: Discussionmentioning
confidence: 99%
“… 1 In particular, high‐grade non‐muscle‐invasive bladder cancer was reported to be the most frequent among types of bladder cancer, and most of the cases occur following kidney transplantation. 2 Herein, we report a case of bladder cancer that emerged following bilateral lung transplantation and bone marrow transplantation.…”
Section: Introductionmentioning
confidence: 99%